Appointments: President Malaysian Natural Product Society (MNPS) 2020-2022 - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
Congratulations to Professor Dr. Nor Hadiani Ismail on her appointment as President of the Malaysian Natural Product Society (MNPS) for the 2020–2022 term. She is a distinguished academic at Universiti Teknologi MARA (UiTM) and a researcher at the Atta-ur-Rahman Institute for Natural Product Discovery (AuRIns), Faculty of Applied Sciences.